Antiferroelectric domain modulation enhancing energy storage performance by phase-field simulations - Ke Xu; Shiyu Tang; Changqing Guo; Yu Song; Houbing Huang (Journal of Materiomics)
Antiferroelectric materials represented by PbZrO3(PZO) have excellent energy storage performance and are expected to be candidates for dielectric capacitors. It remains a challenge to further enhance the effective energy storage density and efficiency of PZO-based antiferroelectric films through domain engineering. In this work, the effects of three variables, misfit strain between the thin film and substrate, defect dipoles doping, and film thickness, on the domain structure and energy storage performance of PZO-based antiferroelectric materials are comprehensively investigated via phase-field simulations. The results show that applying tensile strain to the films can effectively increase the transition electric field from antiferroelectric to ferroelectric. In addition, the introduction of defect dipoles while applying tensile strain can significantly reduce the hysteresis and improve energy storage efficiency. Ultimately, a recoverable energy density of 38.3 J/cm3 and an energy storage efficiency of about 89.4% can be realized at 1.5% tensile strain and 2% defect dipole concentration. Our work provides a new idea for the preparation of antiferroelectric thin films with high energy storage density and efficiency by domain engineering modulation.